The Jewish community in nineteenth century Palestine: evidence from the Montefiore censuses. Issue 6 (1st November 2016) - Kessler, Daniel
Abstract : Initial findings from five recently transcribed censuses of the Jewish community in nineteenth century Palestine, commissioned by Sir Moses Montefiore. This article discusses each census and presents uncorrected population figures. It describes how the Jewish community was rapidly changing: the population increased almost fourfold between 1839 and 1875, primarily due to immigration from Ashkenazi countries. The Jewish community was majority Ashkenazi by 1875. Analysis of the census data gives us detailed information about the community, such as the fact that Ashkenazim were significantly more likely than Sephardim to be engaged in full-time Torah study, whereas individuals who had immigrated to the land of Israel were slightly less likely. It also suggests that immigrations occurred at all ages, although the average age of an immigrant when they came to Palestine was 36.